2009
DOI: 10.1016/j.pnpbp.2009.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Acute harmine administration induces antidepressive-like effects and increases BDNF levels in the rat hippocampus

Abstract: Harmine is a beta-carboline alkaloid that inhibits monoamine reuptake systems. Findings point to an antidepressant effect of the compounds that increases the levels of monoamines after monoamine oxidase inhibition. The present study aims to compare the behavioral effects and the BDNF hippocampus levels of acute administration of harmine and imipramine in rats. To this aim, rats were acutely treated with harmine (5, 10 and 15 mg/kg) and imipramine (10, 20 and 30 mg/kg) and animal behavior was assessed in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 36 publications
2
110
2
4
Order By: Relevance
“…Effect of harmine on animal behavior was assessed in the forced swimming and open-field tests, and the results showed harmine reduced immobility time and increased both climbing and swimming time of rats, compared to saline group. Harmine at a higher dose level also increased brain-derived neurotrophic factor protein levels in the rat hippocampus [23] . Effects of harmine on apomorphine-induced pecking behavior in chicks were also investigated.…”
Section: Effect Of Harmine On Central Nervous Systemmentioning
confidence: 88%
“…Effect of harmine on animal behavior was assessed in the forced swimming and open-field tests, and the results showed harmine reduced immobility time and increased both climbing and swimming time of rats, compared to saline group. Harmine at a higher dose level also increased brain-derived neurotrophic factor protein levels in the rat hippocampus [23] . Effects of harmine on apomorphine-induced pecking behavior in chicks were also investigated.…”
Section: Effect Of Harmine On Central Nervous Systemmentioning
confidence: 88%
“…9) Harmine is also found in common plant-derived foods and animal tissues, 10) and it has antiplasmodial, antioxidative, antimutagenic and antigenotoxic activities, as well as antidepressant properties. [11][12][13] Several psychiatric conditions, including depression, are closely associated with the circadian clock. 14) Although we previously reported that harmine dose-dependently lengthens the circadian period of Bmal1 expression in NIH 3T3 cells, 15) the effects of harmine on the master clock in the SCN remain unknown.…”
mentioning
confidence: 99%
“…Despite the significant increase in extracellular of DA levels induced by harmine, it had no changes in locomotor activity [46] in the OFT [47]. While it is possible that the MAO-A inhibition of harmine has some functional effect on DA efflux in the striatum in vivo.…”
Section: Discussionmentioning
confidence: 90%